An Alternative In-Home Protocol to Diagnose and Treat Obstructive Sleep Apnea - Tarcya L. G. Couto Patriota; Rodrigo Pinto Pedrosa (Sleep Science)
Objective Obstructive sleep apnea (OSA) is a major public health problem of pandemic proportions. In-laboratory OSA diagnosis and continuous positive airway pressure (CPAP) titration are insufficient, considering the number of patients affected. Finding alternative ways to diagnose and treat OSA is mandatory, especially in this era of the coronavirus disease 2019 (COVID-19) pandemic. The present study aims to describe an alternative in-home protocol to diagnose and treat OSA.